Stroke Rehabilitation: When Should Ambulation Activities Commence? (2002)
Stroke is an important cause of disability worldwide. It results in considerable impairments such as sensory, motor, mental, perceptual and language functions. The motor deficits are characterized by hemiplegia and attendant physical limitation. Independent walking function is a highly desired goal among stroke survivors. It is therefore not surprising that recovery from the illness is often measured using ambulation as yardstick by both the patients and their relatives. This strong desire for ambulation often leads to pressure on the attending physiotherapist to commence ambulation promptly. However, some factors need to be taken into consideration by the physiotherapists before commencing ambulation in stroke rehabilitation. This article looks into issues that should be addressed before training ambulation in stroke patients undergoing rehabilitation.